1993
DOI: 10.1177/41.2.7678268
|View full text |Cite
|
Sign up to set email alerts
|

Expression of plasma membrane Ca++ pump epitopes parallels the progression of enamel and dentin mineralization in rat incisor.

Abstract: We investigated the expression of Ca++ pump epitopes during enamel and dentin mineralization in the rat incisor. Secretory and maturation ameloblasts were studied as well as odontoblasts, using a monoclonal antibody (5F10) against human erythrocyte plasma membrane Ca++, Mg(++)-ATPase. A progressive increase in staining intensity in ameloblasts and the odontoblasts was observed beginning with the onset of mineralization. The mainly membrane-related labeling of ameloblasts showed variable intensity depending on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 13 publications
4
39
0
Order By: Relevance
“…The observed up-regulation and abundance of the FI-13-subunit (2.7% of soluble protein) during enamel maturation is consistent with other evidence indicating that the calcium homeostatic burden [15,16], calcium transport [38] and expression levels of the plasma membrane calcium pump [39] are maximal at this time. However, the particular roles (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…The observed up-regulation and abundance of the FI-13-subunit (2.7% of soluble protein) during enamel maturation is consistent with other evidence indicating that the calcium homeostatic burden [15,16], calcium transport [38] and expression levels of the plasma membrane calcium pump [39] are maximal at this time. However, the particular roles (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Expression of Na ϩ -HCO 3 Ϫ transporters in enamel organ. In the stage of enamel secretion, the most peripheral cells of the enamel organ exhibited positive staining reaction for the electrogenic Na ϩ -HCO 3 Ϫ cotransporter NBCe1 but with a decreasing gradient of expression toward the stratum intermedium (Fig.…”
Section: Immunolocalization Of Na ϩ -K ϩ -Atpase In Enamel Organmentioning
confidence: 99%
“…For example, in mineralization of rat teeth, the Ca2+ pump epitopes appear in paral lel with the progression of mineralization [45], An immunocytochemical study in smooth muscle showed localization of the Ca2+ pump to the caveolae, suggesting that these invaginations of the plasma membrane play a special role in Ca2* transport [46]. An in situ hybridization study of rat isoforms 1, 2 and 3 showed that each isoform had a distinct distribution in rat brain [47], There was a more than 20-fold difference in reactivity be tween the most reactive portion of the brain and the least reactive portion, suggesting high ly specialized involvement of this Ca2+ pump in brain function.…”
Section: Other Recent Localization Studiesmentioning
confidence: 99%